Good Girls: Gender-Specific Interventions in Juvenile Court - Gamal, Fanna (Columbia Journal of Gender and Law, 2018)
In the juvenile legal system, many jurisdictions are adopting interventions that target girls for specialized treatment. The proliferation of so-called Girls Courts—or specialty courts designed to address the specific challenges faced by system-involved girl—is one such intervention. Girls Court rejects gender-blindness in the juvenile justice system in order to address the unique needs of system-involved girls. This Article enlists Critical Race Feminism to argue that, although well intentioned, these gender-specific juvenile courts enlist harmful gender stereotypes to guide girls towards an antiquated and hegemonic form of femininity. By examining the underlying assumptions that drive Girls Court, this Article assesses the line between gender-consciousness and gender stereotyping and critiques the role of law in entrenching harmful notions about what “good girls” ought to be. Lifting ideologies from problem-solving courts, Girls Court purports to serve the most at-risk girls, with some jurisdictions placing special emphasis on holistic intervention for child victims of sexual exploitation. Girls Court targets girls, mostly girls of color, for enhanced scrutiny and surveillance. Although heightened services are needed for girls battling intersecting forms of oppression, this Article argues that Girls Court exemplifies important limitations to gender-specific reform. While the court’s approach rightly acknowledges the role of gender in shaping outcomes for young people, it also targets girls for intrusive and punitive methods of social control. Girls Court funnels girls towards a very specific notion of girlhood—one centered in white, middle-class notions of femininity. Through criminalization, an emphasis on sexual purity, and a desire to instill obedience, Girls Court advances certain subordinating stereotypes about girls, particularly girls of color. At its core, this Article argues for an increased duty of care when it comes to programming for girls. It urges a careful examination of all the messages we send, and the values we promote, when we target young girls for intervention.